Extraction of Eutectogel-Carrageenan from Kappaphycus alvarezii using Natural Deep Eutectic Solvent (NADES) Assisted by Ultrasonication - Enda, Dion Kurnia Alfarobi; Santoso, Joko; Uju, Uju; Ramadhan, Wahyu (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
The extraction process of carrageenan from red seaweed (Kappaphycus alvarezii) still predominantly employs conventional solvents, which leave residues that pose potential risks to human health and the environment. Natural Deep Eutectic Solvents (NADES) are green solvents that are biodegradable, biocompatible, and sustainable, offer a promising alternative. The process of extracting carrageenan polysaccharides using NADES enables simultaneous synthesis-extraction (SSE). This process operates through supramolecular interactions and facilitates in situ gel formation, resulting in a Marine Eutectogel based on carrageenan, referred to as Eutectogel-Carrageenan. This study aims to determine the optimal extraction conditions, in terms of temperature and time, for the characteristics of the Eutectogel-Carrageenan-NADES (ECN) produced, and to compare them with those of the Eutectogel-Carrageenan-Commercial (ECC). The research process includes sample preparation, NADES preparation, Eutectogel- Carrageenan extraction using NADES assisted by ultrasonication, and characterization. The optimal condition was established at 80°C for 60 minutes, yielding ECN with a moisture content of 18.93%, yield of 28.81% (db), and viscosity of 5.82 cP. Comparative analyses showed that ECN had a slightly lower sulfate content (3.96% db) and nearly identical functional group spectra compared to ECC, along with rheological properties of lower rigidity and a lower melting point. These findings confirm that ECN produced under optimal NADES-assisted ultrasonication exhibits comparable quality to ECC. This study demonstrates, for the first time, feasibility ofsimultaneous synthesis–extraction of carrageenan eutectogels using NADES, offering a sustainable approach with concrete prospects for food, pharmaceutical, and biomedical applications.